2021
DOI: 10.1002/jsfa.11565
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and antioxidant effects of inoculation with arbuscular mycorrhizal fungi in crops of flesh‐coloured Solanum tuberosum treated with fungicides

Abstract: BACKGROUND: Solanum tuberosum tubers have higher content of phenolic compounds such as hydroxycinnamic acid derivatives (HCAD) and anthocyanins in coloured genotypes. The use of fungicides for crops is common, but there are few studies regarding the interaction of fungicides and arbuscular mycorrhizal fungi (AMF). Here, the AMF-plant interactions and the metabolic responses of three potato genotypes with different tuber colorations (VR808, CB2011-509 and CB2011-104) inoculated with Claroideoglomus claroideum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 45 publications
5
21
3
Order By: Relevance
“…Arbuscular mycorrhizal symbiosis activates the defense mechanism in host plants, increasing the antioxidant activity of phenolic compounds and improving plant growth [ 23 , 24 ]. Fungicide application may influence AM symbiosis, although the results are quite varied depending on the active ingredient, dose, timing of application, mode of application, and environmental conditions [ 19 , 20 ]. Additionally, it is well documented that plant genotype can influence AM symbiosis [ 19 , 21 ], similar to the use of commercial fungicides as MONCUT or ReflectXtra [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Arbuscular mycorrhizal symbiosis activates the defense mechanism in host plants, increasing the antioxidant activity of phenolic compounds and improving plant growth [ 23 , 24 ]. Fungicide application may influence AM symbiosis, although the results are quite varied depending on the active ingredient, dose, timing of application, mode of application, and environmental conditions [ 19 , 20 ]. Additionally, it is well documented that plant genotype can influence AM symbiosis [ 19 , 21 ], similar to the use of commercial fungicides as MONCUT or ReflectXtra [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fungicide application may influence AM symbiosis, although the results are quite varied depending on the active ingredient, dose, timing of application, mode of application, and environmental conditions [ 19 , 20 ]. Additionally, it is well documented that plant genotype can influence AM symbiosis [ 19 , 21 ], similar to the use of commercial fungicides as MONCUT or ReflectXtra [ 22 ]. According to Hage-Ahmed et al, (2019) [ 21 ], some AMF species are more resistant to certain fungicides, whereas others appear to have a neutral effect on AM colonization, and others seem to influence AM symbiosis in a positive manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, the presence of quercetin derivatives and chlorogenic acids has been reported in leaves [ 24 ]. In the roots, their presence is primarily due to exudates of oxalic acid, while in tubers, the contents of these compounds depend on the plant variety, highlighting the presence of chlorogenic acids, such as 5-caffeoylquinic acid, and anthocyanins, such as those derived from petunidins, [ 25 ]. Under drought stress, the total phenol content in Solanum lycopersicum plants increases between 50% and 83% compared to the control [ 26 ].…”
Section: Introductionmentioning
confidence: 99%